Better off dead [videorecording (DVD)] - Holland, Savage Steve; Cusack, John, 1966-; Stiers, David Ogden; Franklin, Diane, 1962-; Darby, Kim, 1947- (Widescreen DVD collection., 2002)
After his girlfriend ditches him for a boorish ski jock, Lane decides that suicide is the only answer. However, his increasingly inept attempts only bring him more agony and embarrassment. Filled with the wildest teen nightmares, a family you can't help but identify with, and a host of wonderful comic characters, Savage Steve Holland's writing/directorial debut is a masterful look at those painfully funny teen years.